Reconceptualizing power and gendered subjectivities in domestic cooking spaces. (October 2014) - Meah, Angela
Drawing on evidence from the Global North and South, this paper explores the power dynamics of domestic kitchens in different geographical contexts. Noting the gendered nature of domesticity, it contrasts those perspectives which regard women's primary responsibility for foodwork as inherently oppressive, with others which see kitchens and associated domestic spaces as sites of potential empowerment for women. The paper explores the complex, spatially-distributed, character of power surrounding domestic foodwork, decentring Anglo-American understandings of the relationship between gender, power and domestic space by foregrounding the experiences of a range of women from across the globe. The paper also examines the increasing role of men in domestic settings, particularly in the Global North, assessing the extent to which their engagement in cooking and other domestic practices may be challenging conventional understandings of the relationship between gender, power and space. Focusing on the spatial dynamics of the domestic kitchen, this paper advances a more nuanced understanding of the co-constitutive nature of the relationship between gender and power, including the instabilities and slippages that occur in the performance of various domestic foodwork tasks. The paper advocates future research on the boundaries of home, work and leisure, focusing on their significance in the constitution and transformation of male and female subjectivities.